Phenomenon of Procrastination in Modern Psychology: Theoretical Fundamentals of the Research - Onipko, Zoriana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
The article is devoted to the analysis of the phenomenon of procrastination in the historical context. The peculiarities of defining this concept in the works of Ukrainian and foreign researchers are considered. Different definitions of the phenomenon of procrastination are analyzed and it is established that there is no single approach to its definition. However, it was found that procrastination has always been characterized by two aspects: voluntary postponement of intention and the presence of psychological discomfort associated with postponement of such intention. The analysis of the reasons of its occurrence is carried out; it was found that there is no consensus on the factors that cause and / or exacerbate procrastination. The characteristic features of this phenomenon and features of manifestation are investigated. The main approaches to the study of procrastination are analyzed: psychodynamic, behavioral, cognitive, subjective, motivational, psychophysiological. Possible negative consequences for the personality are revealed, among which are anxiety, stress, loss of productivity, psychosomatic disorders. The main types of procrastination are considered. It was found that some of the most common reasons for procrastination are: the difficulty of the task, fear of failure and success, perfectionism, insecurity, inability to plan and organize their activities, improper motivation, impulsiveness and others. It has been established that procrastination is a complex, heterogeneous phenomenon that includes a number of components and extends to various spheres of human life. The relationship between the concepts of procrastination and laziness is analyzed. It is established that they are based on various psychological mechanisms. Prospects for further research are identified.